EIF2α phosphorylation is regulated in intracellular amastigotes for the generation of infective Trypanosoma cruzi trypomastigote forms - Castro Machado, Fabricio; Bittencourt-Cunha, Paula; Malvezzi, Amaranta Muniz; Arico, Mirella; Radio, Santiago; Smircich, Pablo; Zoltner, Martin; Field, Mark C; Schenkman, Sergio (Cellular microbiology, 2020)
Trypanosomatids regulate gene expression mainly at the post-transcriptional level through processing, exporting and stabilising mRNA and control of translation. In most eukaryotes, protein synthesis is regulated by phosphorylation of eukaryotic initiation factor 2 (eIF2) at serine 51. Phosphorylation halts overall translation by decreasing availability of initiator tRNAmet to form translating ribosomes. In trypanosomatids, the N-terminus of eIF2α is extended with threonine 169 the homologous phosphorylated residue. Here, we evaluated whether eIF2α phosphorylation varies during the Trypanosoma cruzi life cycle, the etiological agent of Chagas' disease. Total levels of eIF2α are diminished in infective and non-replicative trypomastigotes compared with proliferative forms from the intestine of the insect vector or amastigotes from mammalian cells, consistent with decreased protein synthesis reported in infective forms. eIF2α phosphorylation increases in proliferative intracellular forms prior to differentiation into trypomastigotes. Parasites overexpressing eIF2αT169A or with an endogenous CRISPR/Cas9-generated eIF2αT169A mutation were created and analysis revealed alterations to the proteome, largely unrelated to the presence of μORF in epimastigotes. eIF2αT169A mutant parasites produced fewer trypomastigotes with lower infectivity than wild type, with increased levels of sialylated mucins and oligomannose glycoproteins, and decreased galactofuranose epitopes and the surface protease GP63 on the cell surface. We conclude that eIF2α expression and phosphorylation levels affect proteins relevant for intracellular progression of T. cruzi.
Keywords: mutace; Virulence; Chagasova nemoc; Animals; protozoální proteiny; buněčné linie; CRISPR-Cas systémy; proteosyntéza; phosphorylation; Cell Line, Tumor; proteom; CRISPR-Cas Systems; Parasitemia; Proteome; Protozoan Proteins; nádorové buněčné linie; lidé; Mutation; Cell Line; Phosphorylation; stadia vývoje; virulence; regulace genové exprese; eukaryotický iniciační faktor 2; eIF2; fosforylace; translation; differentiation; Protein Biosynthesis; Chagas Disease; Gene Expression Regulation; zvířata; Life Cycle Stages; Eukaryotic Initiation Factor-2; parazitemie; Trypanosoma cruzi; Humans